P554 Vedolizumab Associated quality of Life and inflammatory bowel disease control Upon Entering a subcutaneous switching program (VALUE) – Results from a multi-centre UK study. (21st January 2022) - Lim, S; Gros Alcade, B; Lehmann, A; Lindsay, J; Gaya, D; Caulfield, L; Dhar, A; Ritchie, S; Limdi, J; Taylor, J; Raine, T; Balendran, K; et al.
Abstract: Background: Vedolizumab, a gut-selective monoclonal antibody targeting α4β7-integrin, was recently licenced as a subcutaneous (SC) preparation after demonstrating efficacy compared to placebo at maintaining remission in IBD patients who had a clinical response to intravenous (IV) induction therapy. We aimed to assess real-world experience of switching patients to SC administration. Methods: Patients across 10 UK centres who had completed induction with IV vedolizumab were offered SC therapy. Demographic data and baseline disease characteristics (disease type and behaviour, medication history) were collected, alongside biochemical markers (C-reactive protein, faecal calprotectin), disease activity scores (SCCAI, partial Mayo or modified Harvey Bradshaw Index) and quality of life scores (IBD-Control-8) at baseline (defined as the first dose of SC medication), 8 and 24. Data was also collected on drug persistence, hospital admissions, steroid use and reported adverse events. Results: 351 patients were switched to SC dosing. All had data collected for weeks 0 and 8 and 164 had data at week 24. There were no statistically significant differences in biochemical markers, disease activity scores or quality of life at weeks 0, 8 or 24, nor were there statistically significant differences in rates of biochemical remission or clinical remission. Subcutaneous vedolizumab persistence at week 24 was 86% (141/164), with discontinuation due to disease activity (n=9), adverse events (n=11), non-compliance (n=2) and pregnancy (n=1). Of the 23 who discontinued SC, 12 switched back to IV (4 of whom at an escalated dose), 4 changed to another biologic and 7 stopped/paused biologic therapy. Within the 24-week study period, 7.9% (n=13) required steroids, 2.4% (n=4) had an IBD-related hospital admission and 8.5% (n=14) experienced an adverse reaction of which 7 were injection site-related. One patient experienced an anaphylactoid reaction upon restarting IV vedolizumab. There were no statistically significant associations between baseline characteristics (including clinical or biochemical markers, duration of vedolizumab use or prior ant-TNF exposure) and week 32 outcomes. Conclusion: Switching from IV to SC vedolizumab appears to maintain rates of remission with no significant changes in biochemical markers, clinical scores or quality of life, with SC administration persistence of 86% at week 24. Further long-term data on safety is required.